The smoothness criterion as a trend diagnostic. (12th February 2006) - Fogarty, P.; Weber, N. C.
Abstract : The smoothness criterion is used in the design of symmetric moving average trend filters in time series and in graduation in actuarial studies. This measure of smoothness is used to motivate a diagnostic for determining the order of local polynomial trend.